Fundamentals of laser micromachining - Schaeffer, Ronald D. (CRC Press, 2012)
Due to their flexible and efficient capabilities, lasers are often used over more traditional machining technologies, such as mechanical drilling and chemical etching, in manufacturing a wide variety of products, from medical implants, gyroscopes, and drug delivery catheters to aircraft engines, printed circuit boards, and fuel cells. Fundamentals of Laser Micromachining explains how laser technology is applied to precision micromachining. The book combines background on physics, lasers, optics, and hardware with analysis of markets, materials, and applications. It gives sufficient theoretical background for readers to understand basic concepts while including a further reading appendix for those interested in more detailed theoretical discussions. After reviewing laser history and technology, the author compares available laser sources, including CO2, excimer, Nd:YAG, fiber, and short pulse. He also addresses topics crucial to obtaining good processing results, such as IR and UV material-photon interaction, basic optical components, and system integration. The text goes on to cover real-world applications in the medical, microelectronics, aerospace, and other fields. It concludes with details on processing many common materials, such as metals, silicon, ceramics, and glasses. For engineers and project managers, this book provides the foundation to achieve cost-effectiveness, the best edge quality, and the highest resolution in small-scale industrial laser machining. It will help you select the correct kind of laser for your application and identify real opportunities for growth in the marketplace.